Knowledge and Experience of Community Health Volunteer (Cadre) on Type 2 Diabetes Mellitus Management in Yogyakarta - Primanda, Yanuar; Fatah, Desy Ivani (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is a chronic disease that requires long-term and comprehensive management. People with T2DM play a significant role in managing their condition and day-to-day life adjustment related to T2DM. In the Indonesian context, community health volunteers (cadres) roles are imperative because the community can influence day-to-day health care. AIM: The study aimed to describe the knowledge and experience of cadre on T2DM management in Yogyakarta, Indonesia. METHODS: It was a descriptive study with a cross-sectional approach. Five primary health-care center (Puskesmas) areas in Bantul district were selected based on their high population, including Kasihan 2, Jetis 1, Sedayu 1, Jetis 2, and Imogiri 2 areas. Sixty-eight cadres from those five areas were enrolled in this study through accidental sampling. The data were collected using questionnaires and analyzed using descriptive statistics. RESULTS: The results showed that the average age of cadres was 43 years old (20–64 years), with more than half of them graduating from high school, unemployed (61.8%), and never received education about DM and its management (51.5%). Forty-two cadres (61.8%) had a moderate level of knowledge, and 64.7% had inadequate experience in T2DM management. CONCLUSION: Knowledge and experience of cadre regarding T2DM management in Yogyakarta need to be increased. Further research is needed to examine certain training programs’ effects to improve cadre’s knowledge and experience in T2DM.